Making Áztlán : ideology and culture of the Chicana and Chicano movement, 1966-1977 - Gómez-Quiñones, Juan; Vásquez, Irene (University of New Mexico Press, 2014)
"This book provides a long-needed overview of the Chicana and Chicano movement's social history as it grew, flourished, and then slowly fragmented. The authors examine the movement's origins in the 1960s and 1970s, showing how it evolved from a variety of organizations and activities united in their quest for basic equities for Mexican Americans in U.S. society"--Provided by publisher
Keywords: Chicano movement.; Mexican Americans -- Politics and government -- 20th century.; Mexican Americans -- Civil rights -- History -- 20th century.; Mexican Americans -- Social conditions -- 20th century.; Mexican Americans -- Ethnic identity.; United States -- Ethnic relations -- History -- 20th century.; United States -- Social conditions -- 20th century.; Américains d'origine mexicaine -- Droits -- Histoire -- 20e siècle.; Américains d'origine mexicaine -- Conditions sociales -- 20e siècle.; Américains d'origine mexicaine -- Identité ethnique.; États-Unis -- Relations interethniques -- Histoire -- 20e siècle.; États-Unis -- Conditions sociales -- 20e siècle.; HISTORY -- United States -- State & Local -- General.; Chicano movement; Ethnic relations; Mexican Americans -- Civil rights; Mexican Americans -- Ethnic identity; Mexican Americans -- Politics and government; Mexican Americans -- Social conditions; Social conditions; United States; Identität; Ethnische Beziehungen; Chicanos; Bürgerrecht; USA; 1900-1999; History